3D direct writing fabrication of electrodes for electrochemical storage devices - Wei, Min; Zhang, Feng; Wang, Wei; Alexandridis, Paschalis; Zhou, Chi; Wu, Gang (Journal of power sources, 2017)
Among different printing techniques, direct ink writing is commonly used to fabricate 3D battery and supercapacitor electrodes. The major advantages of using the direct ink writing include effectively building 3D structure for energy storage devices and providing higher power density and higher energy density than traditional techniques due to the increased surface area of electrode. Nevertheless, direct ink writing has high standards for the printing inks, which requires high viscosity, high yield stress under shear and compression, and well-controlled viscoelasticity. Recently, a number of 3D-printed energy storage devices have been reported, and it is very important to understand the printing process and the ink preparation process for further material design and technology development. We discussed current progress of direct ink writing technologies by using various electrode materials including carbon nanotube-based material, graphene-based material, LTO (Li4Ti5O12), LFP (LiFePO4), LiMn1-xFexPO4, and Zn-based metallic oxide. Based on achieve electrochemical performance, these 3D-printed devices deliver performance comparable to the energy storage device fabricated using traditional methods still leaving large room for further improvement. Finally, perspectives are provided on the potential future direction of 3D printing for all solid-state electrochemical energy storage devices. [Display omitted] •The 2D and 3D structures of energy storage devices are reviewed.•Energy storage devices are printed using different materials by 3D direct writing.•The 3D devices deliver a better performance than traditional fabrication methods.